Environmental Risk Assessment of Genetically Modified Organisms. Volume 2: Methodologies for Assessing Bt Cotton in Brazil 2006
DOI: 10.1079/9781845930004.0175
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of Bt cotton on generalist arthropod predators.

Abstract: This chapter illustrates the particular application of the scientific methodology (used during the pre-release stages of Bt cotton) supporting the risk assessment of nontarget organisms and biodiversity to generalist arthropod predators in Brazil. The steps in the methodology (i.e. species selection, listing and prioritizing nontarget species and processes, identifying trophically mediated exposure pathways to transgenic plant and transgene products, identifying possible adverse effect scenarios for trophicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Nontarget species likely to be highly exposed to the environmental stressor and to contribute significantly to the ecological function are selected. For example, C. sanguinea is a common arthropod predator in cotton in Brazil (Faria et al 2006) and provides important biological control of cotton aphids. As it is likely to be exposed to Bt cotton through bi-or tritrophic exposure, it could be used to evaluate the potential effects of Bt cotton on biological control agents in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Nontarget species likely to be highly exposed to the environmental stressor and to contribute significantly to the ecological function are selected. For example, C. sanguinea is a common arthropod predator in cotton in Brazil (Faria et al 2006) and provides important biological control of cotton aphids. As it is likely to be exposed to Bt cotton through bi-or tritrophic exposure, it could be used to evaluate the potential effects of Bt cotton on biological control agents in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Ladybeetles are widely regarded as important biological control agents in agricultural habitats. Five species dominate the ladybeetle community associated with cotton in Brazil (Faria et al., ), and an analysis of the behavioral and physiological traits of these species (Oliveira et al., ), and the community composition on cotton in Central Brazil (EMG Fontes, CSS Pires & ER Sujji, unpubl.) has indicated that C. sanguinea is the most significant coccinellid predator and one of the priority candidates for ecological non‐target risk assessment of genetically modified (GM) cotton (Faria et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Five species dominate the ladybeetle community associated with cotton in Brazil (Faria et al., ), and an analysis of the behavioral and physiological traits of these species (Oliveira et al., ), and the community composition on cotton in Central Brazil (EMG Fontes, CSS Pires & ER Sujji, unpubl.) has indicated that C. sanguinea is the most significant coccinellid predator and one of the priority candidates for ecological non‐target risk assessment of genetically modified (GM) cotton (Faria et al., ). This species is abundant in the tropical and subtropical range of the New World (Gordon, ) and is reported to be a dominant predator in several crops in Florida (USA) (Michaud, ), Central and South America (Vandenberg & Gordon, ), and in Brazil (Santa‐Cecilia et al., ; Oliveira et al., ).…”
Section: Introductionmentioning
confidence: 99%